Para além da inovação e do empreendedorismo no capitalismo brasileiro - Janaynna de Moura Ferraz (2019)
The continuous need for innovation coupled with individualized and precarious work activities, although socially dependent, is made possible by the automation of the management of the productive process and by the attractiveness of the higher value generated by the expansion of the market (increasingly worldwide) throughout the cycle from capital, from production to the realization of more value in the sphere of circulation. We start from the discussion of the process of work and valorization process elaborated from the critique of political economy to demonstrate the role of the new in the human self-production and, more specifically, in the specifically capitalist production, in which the innovation process is subordinated to the values to the detriment of the usefulness of the product of labor. This process complies with the general law of capitalist accumulation whose innovation is a sine qua non for extraordinary profits at the time of intracapitalist competition and, also, a primordial element for the development of the productive forces. In modern times, innovation is alluded to as the engine of economic growth, whose role is attributed to entrepreneurs. We elaborate the thesis that the entrepreneurial practice corresponds to an important unfolding of the development of the productive forces that reorganizes production, distribution, circulation and consumption in order to raise the rates of extraction of more value; whether through innovation, in the quest for extraordinary profit intracapitalist; be it through precarious entrepreneurship, which contributes so much to the acceleration of the cycle of capital as it lowers the price of the labor force, intensifying the pauperization of the working class. We talk about these bourgeois justifications for entrepreneurial practice, demonstrating that they are not means for the reduction of misery, but are instead the means for the expansion of capital. We expose the critique of the apologetics of the new, demonstrating how the idea of entrepreneurial spirit was consolidated, as well as its function in the practice of entrepreneurship and class struggle. In the sequence, the particularity of the Brazilian entrepreneurial practice is analyzed and discussed both from its historical formation and in comparison with other countries, to show how the entrepreneurial practice can be both for innovation and for precarious work (precarious entrepreneurship). We conclude that these two functions of entrepreneurial practice contribute to the reproduction of capital by acting more in the sphere of circulation at the moment of realization of value and the lowering of the workforce, while at the same time innovating. Finally, we place the entrepreneurial practice in the class struggle to discuss its potentialities and limits of radical social transformation.